Strategi Mengatasi Out of Stock (OOS) Untuk Peningktan Service Level Warehouse Di PT XYZ Cabang Malang - muhammadrezapahlevi Reza pahlevi (Jurnal Sekretaris dan Administrasi Bisnis, 2026)
PT XYZ is a leading retail company in Indonesia, widely recognized by the public. The company offers a wide range of products to meet customers' daily needs. This study aims to analyze and evaluate the impact of optimizing inventory turnover on improving the warehouse service level at PT XYZ. Inventory turnover, particularly the ToTi process or PKM Review, is a complex procedure that significantly affects warehouse operational efficiency and customer satisfaction. Currently, PT XYZ faces challenges related to low warehouse service levels due to suppliers' inability to meet the company's demands, leading to stockouts in the warehouse. Based on the research findings, recommendations for inventory turnover, including the ToTi process or PKM Review, have positively contributed to improving the warehouse service level at PT XYZ. The results indicate that by optimizing the ToTi process and PKM Review, PT XYZ successfully increased the warehouse service level from 77% to 100%, and the PKM Review outcomes improved from 1,100 to 2,300. This strategy involves enhancing stock fulfillment as well as improving communication and collaboration with related warehouses. In the long term, the findings of this study are expected to further improve the warehouse service level and reduce losses for PT XYZ